Ability of Activity Daily Living in Stroke Patients Based on Katz Indekz Assessment: Case Study - Cahyati, Yanti; Sejati, Alzahra Putri; Rahman, Arip (Journal of Smart Nursing and Health Science, 2023)
Background: Stroke is a clinical sign in the form of disruption of brain function, which can cause symptoms including balance disorders including muscle weakness, processes in thinking, the brain's ability to store memory, fluency of speech, to loss of body balance. Research results of the Ministry of Health in 2018, the prevalence of stroke patients in Indonesia has increased by 10.9%. Of stroke patients, 80% experience weakness on one side of their body, which results in a lack of muscle contractions due to the cessation of blood supply to the brain. The impact of weakness experienced by stroke patients can cause imbalances and disrupt the ability to carry out daily activities. Conducting an Activities Daily Living (ADL) assessment is one form of measuring independence or functional ability. Aims: The purpose of research is to determine the level of independence of stroke patients in carrying out daily activities. Method: This research uses a qualitative design with a case study approach; the process is carried out for 2 weeks, from April 6, 2023, to April 19, 2023. The presentation of data on these two respondents used the Katz index instrument. Results: The level of independence of Respondent 1 is included in category F, which is dependent on bathing, dressing, going to the restroom, and defecating / bath. In contrast, respondent 2 is included in class G, namely total dependence, where patients cannot eat, continent, move places, go to the restroom, bathe, and dress independently. Conclusion: The case study results obtained the level of independence of the two respondents with the category of Total dependence.